America's beginnings : the dramatic events that shaped a nation's character - Williams, Tony, 1970- (Rowman & Littlefield Publishers ; in association with the Colonial Williamsburg Foundation, 2010)
At a time when surveys reveal that Americans know less and less about our past, Tony Williams provides entertaining and informative descriptions of 50 key events-some known and some forgotten- that shaped colonial and revolutionary America, from the Mayflower Compact to the Annapolis Convention.